Adhesive and manufacturing method thereof, separator, electrode assembly, battery cell, battery and power consuming device

JP2025505074AActive Publication Date: 2025-02-21CONTEMPORARY AMPEREX TECHNOLOGY (HONG KONG) LIMITED
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023570237
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-01-04
Filing Date
2023-06-13
Publication Date
2025-02-21
Estimated Expiration
2043-06-13

Smart Images

  • Figure 2025505074000001_ABST
    Figure 2025505074000001_ABST
Patent Text Reader

Abstract

The present application relates to the field of battery technology, in particular to an adhesive and its manufacturing method, and a separator, an electrode assembly, a battery cell, a battery and a power consumption device containing the adhesive. The adhesive includes a core layer structure and a shell layer structure provided on the surface of the core layer structure, the core layer structure includes a polyvinylidene fluoride polymer, and the shell layer structure includes a polyacrylate-based polymer, and the polyvinylidene fluoride is a homopolymer with a crystallinity of about 50% and insufficient adhesive strength. Therefore, the present application improves the crystallinity of the polyvinylidene fluoride polymer in the adhesive with the core-shell structure by coating the polyvinylidene fluoride polymer with a polyacrylate-based polymer to obtain an adhesive with a core-shell structure, thereby realizing the improvement of the adhesive performance of the adhesive with the core-shell structure, and the adhesive improves the adhesive strength between the separator and the electrode plate.
Need to check novelty before this filing date? Find Prior Art

Description

CROSS-REFERENCE TO RELATED APPLICATIONS

[0001] This application claims priority to a Chinese patent application filed on January 4, 2023, bearing application number 202310010451.2, the entire contents of which are incorporated herein by reference. [Technical field]

[0002] The present application relates to the field of battery technology, and in particular to adhesives and methods for making same, as well as separators, electrode assemblies, battery cells, batteries and power consuming devices. [Background technology]

[0003] With the rapid increase in portable electronic devices, electric vehicles, etc., the demand for power batteries is constantly increasing, and the electrochemical performance of batteries is also attracting more and more attention.

[0004] Currently, the battery core of the battery has an opening problem, that is, gaps easily form between the plates and the separator, which leads to poor battery cycling performance. Summary of the Invention

[0005] The main object of the present application is to provide an adhesive that is intended to improve the adhesive strength between the separator and the electrode plate, thereby improving the cycle performance of the battery.

[0006] In order to achieve the above object, the present application provides an adhesive, the adhesive comprising a core layer structure and a shell layer structure provided on a surface of the core layer structure, the shell layer structure comprising a polyacrylate-based polymer, and the core layer structure comprising a polyvinylidene fluoride polymer.

[0007] The adhesive of the present application includes a core layer structure and a shell layer structure provided on the surface of the core layer structure, the core layer structure includes a polyvinylidene fluoride polymer, and the shell layer structure includes a polyacrylate-based polymer, in which polyvinylidene fluoride is a homopolymer with a crystallinity of about 50% and insufficient adhesive strength. Therefore, the present application coats the polyvinylidene fluoride polymer with a polyacrylate-based polymer to obtain a core-shell structured adhesive, thereby improving the crystallinity of the polyvinylidene fluoride polymer in the core-shell structured adhesive and improving the adhesive performance of the core-shell structured adhesive, and this adhesive improves the adhesive strength between the separator and the electrode plate.

[0008] Optionally, the shell layer structure includes a plurality of cases, the plurality of cases being spaced apart from one another on the surface of the core layer structure.

[0009] The polyacrylate-based polymer case is not continuously coated on the surface of the core layer structure, but is attached to the surface of the core layer structure at intervals, and resembles a raspberry-like structure.As can be seen, the shell layer structure is equivalent to a plurality of cases, and there are gaps between adjacent cases, and the surface of the core layer structure can be exposed at the gaps, and thus the polyvinylidene fluoride polymer core layer structure is exposed, and the core layer structure has relatively good adhesion, so the core layer structure exposed between the cases can also reinforce the adhesion performance, and the raspberry-like core-shell structure has a larger specific surface area than the core layer structure completely coated with the shell layer, and thus the surface structure with adhesive function can play a greater adhesive role.

[0010] Alternatively, the mass ratio of the polyvinylidene fluoride polymer to the polyacrylate-based polymer is (2-100):1, and optionally (10-80):1.

[0011] In order to obtain the above-mentioned core-shell structure of raspberry-like structure, the mass of polyvinylidene fluoride polymer is greater than the mass of polyacrylate-based polymer, and the mass of core layer structure is greater than the mass of shell layer structure, so that the surface of the core layer structure is not completely covered with the shell layer structure, so that some structure is exposed on the surface of the core layer structure, thereby obtaining the above-mentioned core-shell structure of raspberry-like structure. Here, the mass of the core layer structure is greater than the mass of the shell layer structure, and the mass ratio of the core layer structure to the shell layer structure can be (2 to 100): 1, and in the above (2 to 100): 1, the value includes the minimum and maximum values ​​of this range, and each value between such minimum and maximum values, and specific examples include, but are not limited to, the point values ​​in the examples and 2: 1, 10: 1, 20: 1, 30: 1, 40: 1, 50: 1, 60: 1, 70: 1, 80: 1, 90: 1, 100: 1, etc.

[0012] Optionally, the mass ratio of the polyvinylidene fluoride polymer to the polyacrylate-based polymer is (10-80:1).

[0013] In order to obtain the above-mentioned raspberry-shaped core-shell structure, the mass of the polyvinylidene fluoride polymer is greater than the mass of the polyacrylate-based polymer, and the mass of the core layer structure is greater than the mass of the shell layer structure, so that the surface of the core layer structure is not completely covered with the shell layer structure, so that some structure is exposed on the surface of the core layer structure, thereby obtaining the above-mentioned raspberry-shaped core-shell structure. Here, the mass of the core layer structure is greater than the mass of the shell layer structure, and the mass ratio of the core layer structure to the shell layer structure can be (10-80):1, and in the above (10-80):1, the value includes the minimum and maximum values ​​of this range, and each value between such minimum and maximum values, and specific examples include, but are not limited to, the point values ​​in the examples and 10:1, 20:1, 30:1, 40:1, 50:1, 60:1, 70:1, 80:1, etc.

[0014] Optionally, the adhesive has a volume average particle size Dv50 of 0.5 μm-50 μm, optionally 7 μm-8 μm.

[0015] Theoretically, the volume average particle diameter Dv50 of the adhesive in the present application may be less than 0.5 μm or more than 50 μm. However, considering that the adhesive in the present application is used in a separator, the volume average particle diameter Dv50 of the adhesive cannot be too large or too small. If the adhesive is too small, it is likely to block the pores of the separator, reducing the permeability of lithium ions through the separator. If the adhesive is too large, a thick coating will be formed when the adhesive is applied to the separator. Since this affects the energy density of the battery produced later, the volume average particle diameter Dv50 of the adhesive is 0.5 μm-50 μm, and in the above 0.5 μm-50 μm, the value includes the minimum and maximum values ​​of this range, and each value between such minimum and maximum values. Specific examples include, but are not limited to, the point values ​​in the examples and 0.5 μm, 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, etc.

[0016] Optionally, the adhesive has a volume average particle size Dv50 of 7 μm-8 μm.

[0017] When the volume average particle diameter Dv50 of the adhesive is 7 μm-8 μm, the performance of the resulting separator is excellent, and in the above 7 μm-8 μm, the values ​​include the minimum and maximum values ​​of this range, and each value between such minimum and maximum values, and specific examples include, but are not limited to, the point values ​​in the examples and 7 μm, 7.5 μm, 8 μm, etc.

[0018] Optionally, the constituent monomers of the polyacrylate-based polymer include a first polymerizable flexible monomer, a second polymerizable polar monomer, and a third polymerizable molecular weight adjusting monomer.

[0019] The constituent monomers of the polyacrylate polymer in the present application include a first polymerizable flexible monomer, a second polymerizable polar monomer, and a third polymerizable molecular weight adjusting monomer. By crosslinking the three types of monomers to obtain a polymer, the molecular weight and glass transition temperature of the polymer can be controlled, thereby improving the adhesive performance of the adhesive.

[0020] Alternatively, the molar ratio of the first polymerizable flexible monomer to the second polymerizable polar monomer to the third polymerizable molecular weight adjusting monomer is 1:(0.01-0.8):(0.01-0.15), and optionally 1:(0.05-0.7):(0.05-0.12).

[0021] When the molar ratio of the first polymerizable flexible monomer, the second polymerizable polar monomer, and the third polymerizable molecular weight adjusting monomer is 1:(0.01-0.8):(0.01-0.15), the adhesive has excellent adhesion effect. In the above 1:(0.01-0.8):(0.01-0.15), the values ​​include the minimum and maximum values ​​of this range, and each value between such minimum and maximum values. Specific examples are the point values ​​in the examples and 1:0. This includes, but is not limited to, 01:0.01, 1:0.1:0.01, 1:0.4:0.01, 1:0.8:0.01, 1:0.01:0.05, 1:0.01:0.1, 1:0.01:0.15, 1:0.1:0.01, 1:0.1:0.05, 1:0.1:0.15, 1:0.4:0.01, 1:0.4:0.05, 1:0.4:0.15, 1:0.8:0.01, 1:0.8:0.05, 1:0.8:0.15, etc.

[0022] Optionally, the molar ratio of the first polymerizable flexible monomer, the second polymerizable polar monomer, and the third polymerizable molecular weight adjusting monomer is 1:(0.05-0.7):(0.05-0.12).

[0023] When the molar ratio of the first polymerizable flexible monomer to the second polymerizable polar monomer to the third polymerizable molecular weight adjusting monomer is 1:(0.05-0.7):(0.05-0.12), the adhesive has excellent adhesion effect. In the above 1:(0.05-0.7):(0.05-0.12), the values ​​include the minimum and maximum values ​​of this range, and each value between such minimum and maximum values. Specific examples include, but are not limited to, the point values ​​in the examples and 1:0.05:0.05, 1:0.1:0.05, 1:0.4:0.05, 1:0.7:0.05, 1:0.1:0.05, 1:0.1:0.1, 1:0.1:0.12, etc.

[0024] Optionally, the structure of the first polymerizable flexible monomer contains an ester bond, the structure of the second polymerizable polar monomer contains a cyano group, and the structure of the third polymerizable molecular weight adjusting monomer contains an amide bond.

[0025] The ester bond can improve the flexibility of the molecular chain, the cyano group can improve the polarity of the monomer, and the amide bond has polarity and is easy to form hydrogen bonds, which can improve the adhesiveness. The first polymerizable flexible monomer contains an ester bond in its structure, the second polymerizable polar monomer contains a cyano group in its structure, and the third polymerizable molecular weight adjusting monomer contains an amide bond, so that the polymer obtained by polymerizing the above three types of monomers can control the molecular weight and glass transition temperature of the polymer, thereby improving the adhesive performance of the adhesive.

[0026] Optionally, the first polymerizable flexible monomer is an acrylate-based monomer, the second polymerizable polar monomer is an acrylonitrile-based monomer, and the third polymerizable molecular weight adjusting monomer is an acrylamide-based monomer.

[0027] The acrylate monomer can improve the swelling resistance of the polymer, and as a flexible monomer segment in the molecular segment, it can adjust the glass transition temperature of the polymer, improve the toughness of the adhesive when applied, and contribute to exerting a good adhesive effect. The acrylonitrile monomer has a highly polar cyano group, which improves the ion conductivity and contributes to improving the adhesiveness. The acrylamide monomer plays the role of adjusting the molecular weight and also has relatively good adhesiveness. The polymer produced by the above three types of monomers can control the molecular weight and glass transition temperature of the polymer, thereby improving the adhesive performance of the adhesive.

[0028] Alternatively, the acrylate monomer may include at least one of methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, n-propyl acrylate, cyclohexyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, isobornyl methacrylate, lauryl methacrylate, 2-hydroxyethyl methacrylate, and 2-hydroxypropyl methacrylate; and / or the acrylonitrile-based monomer includes at least one of acrylonitrile and methacrylonitrile; And / or, the acrylamide-based monomer includes at least one of acrylamide, N-methylolacrylamide, and N-butoxymethacrylamide.

[0029] The acrylate monomer contributes to improving the adhesive properties of the adhesive. The acrylate monomer may include at least one of methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, n-propyl acrylate, cyclohexyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, isobornyl methacrylate, lauryl methacrylate, 2-hydroxyethyl methacrylate, and 2-hydroxypropyl methacrylate. In other words, the constituent monomers of the polyacrylate polymer may include one of the above acrylate monomers, or may include multiple acrylate monomers, and are not specifically limited.

[0030] The acrylonitrile-based monomer contributes to improving the adhesive properties of the adhesive, and the acrylonitrile-based monomer includes at least one of acrylonitrile and methacrylonitrile. In other words, the constituent monomers of the polyacrylate-based polymer may include one of the above acrylonitrile-based monomers or may include multiple of the above acrylonitrile-based monomers, and are not specifically limited.

[0031] The acrylamide monomer contributes to improving the adhesive properties of the adhesive, and the acrylamide monomer includes at least one of acrylamide, N-methylolacrylamide, and N-butoxymethacrylamide. In other words, the constituent monomers of the polyacrylate polymer may include one of the above acrylamide monomers or may include multiple acrylamide monomers, and are not specifically limited.

[0032] Optionally, the polyvinylidene fluoride polymer comprises at least one of vinylidene fluoride polymer, vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-pentafluoropropylene copolymer, vinylidene fluoride-tetrafluoropropylene copolymer, vinylidene fluoride-trifluoropropylene copolymer, vinylidene fluoride-perfluorobutene copolymer, vinylidene fluoride-tetrafluoroethylene copolymer, vinylidene fluoride-trifluoroethylene copolymer, vinylidene fluoride-trifluorochloroethylene copolymer, or vinylidene fluoride-vinyl fluoride copolymer.

[0033] In addition to having good chemical resistance and corrosion resistance, polyvinylidene fluoride polymers also have special properties such as high temperature resistance, oxidation resistance, weather resistance, and radiation resistance, as well as piezoelectric, dielectric, and thermoelectric properties, and are often used in lithium-ion battery separators.

[0034] The polyvinylidene fluoride polymer used in the present application includes at least one of vinylidene fluoride polymer, vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-pentafluoropropylene copolymer, vinylidene fluoride-tetrafluoropropylene copolymer, vinylidene fluoride-trifluoropropylene copolymer, vinylidene fluoride-perfluorobutene copolymer, vinylidene fluoride-tetrafluoroethylene copolymer, vinylidene fluoride-trifluoroethylene copolymer, vinylidene fluoride-trifluorochloroethylene copolymer, or vinylidene fluoride-vinyl fluoride copolymer, i.e., the polyvinylidene fluoride polymer may include one of the above polyvinylidene fluoride polymers, or may include a plurality of the above polyvinylidene fluoride polymers, and is not specifically limited.

[0035] The present application further provides a method for producing an adhesive, Add water, an emulsifier, an initiator, and constituent monomers of polyvinylidene fluoride polymer into a reaction vessel, stir, and heat under reaction pressure to polymerize, thereby obtaining a seed emulsion, which is kept as a reserve; mixing and stirring water, an emulsifier, and a constituent monomer of a polyacrylate-based polymer to obtain a shell layer monomer pre-emulsion, which is used as a reserve; adding the shell layer monomer pre-emulsion, an initiator and water to the seed emulsion, and stirring and heating to react with each other to obtain a core-shell structured adhesive.

[0036] In the present application, a seed emulsion of polyvinylidene fluoride polymer for the core layer is first obtained by emulsion polymerization, and then a polyacrylate-based polymer for the shell layer is prepared on the surface of the core layer structure by emulsion polymerization, and finally an adhesive having a core-shell structure is formed.

[0037] Alternatively, the ratio of the constituent monomer mass of the polyvinylidene fluoride polymer to the constituent monomer mass of the polyacrylate polymer is (2-100:1), and optionally (10-80:1).

[0038] In order to obtain the above-mentioned core-shell structure of raspberry-like structure, the mass of the core layer structure is made larger than the mass of the shell layer structure, so that the surface of the core layer structure is not completely covered with the shell layer structure, so that some structure is exposed on the surface of the core layer structure, thereby obtaining the above-mentioned core-shell structure of raspberry-like structure. Here, the mass of the core layer structure is larger than the mass of the shell layer structure, and the mass ratio of the core layer structure to the shell layer structure can be (2 to 100): 1, and in the above (2 to 100): 1, the value includes the minimum value and the maximum value of this range, and each value between such minimum value and maximum value, and specific examples include, but are not limited to, the point value in the embodiment and 2: 1, 10: 1, 20: 1, 30: 1, 40: 1, 50: 1, 60: 1, 70: 1, 80: 1, 90: 1, 100: 1, etc.

[0039] Optionally, the ratio of the constituent monomer mass of the polyvinylidene fluoride polymer to the constituent monomer mass of the polyacrylate polymer is (10-80:1).

[0040] In order to obtain the above-mentioned core-shell structure of raspberry-like structure, the mass of the core layer structure is made larger than the mass of the shell layer structure, so that the surface of the core layer structure is not completely covered with the shell layer structure, so that some structure is exposed on the surface of the core layer structure, thereby obtaining the above-mentioned core-shell structure of raspberry-like structure. Here, the mass of the core layer structure is larger than the mass of the shell layer structure, and the mass ratio of the core layer structure to the shell layer structure can be (10-80):1, and in the above (10-80):1, the value includes the minimum and maximum values ​​of this range, and each value between such minimum and maximum values, and specific examples include, but are not limited to, the point values ​​in the examples and 10:1, 20:1, 30:1, 40:1, 50:1, 60:1, 70:1, 80:1, etc.

[0041] Optionally, the constituent monomers of the polyvinylidene fluoride polymer include vinylidene fluoride; Alternatively, the constituent monomers of the polyvinylidene fluoride polymer include at least one of vinylidene fluoride, hexafluoropropylene, pentafluoropropylene, tetrafluoropropylene, trifluoropropylene, perfluorobutene, tetrafluoroethylene, trifluoroethylene, trifluorochloroethylene, and vinyl fluoride.

[0042] A polyvinylidene fluoride polymer is a polymer having vinylidene fluoride as a monomer, and the monomer of the polyvinylidene fluoride polymer further includes at least one of hexafluoropropylene, pentafluoropropylene, tetrafluoropropylene, trifluoropropylene, perfluorobutene, tetrafluoroethylene, trifluoroethylene, trifluorochloroethylene, and vinyl fluoride in addition to vinylidene fluoride. That is, the polyvinylidene fluoride polymer may be a homopolymer of vinylidene fluoride or a copolymer of vinylidene fluoride and another fluorine-containing ethylene, and is not specifically limited.

[0043] An embodiment of the present application provides a separator, the separator comprising an adhesive as described above or an adhesive produced by the method for producing an adhesive as described above.

[0044] The separator is coated with the above adhesive, which can improve the adhesive performance between the electrode plate and the adhesive and improve the opening problem in the conventional battery core pre-cold pressing process.

[0045] An embodiment of the present application provides an electrode assembly, the electrode assembly including the separator described above.

[0046] The electrode assembly includes a positive electrode plate, a negative electrode plate, and a separator, and the adhesive is coated on the separator, thereby bonding the electrode plate and the separator together and improving the problem of openings between the electrode plate and the separator.

[0047] An embodiment of the present application provides a battery cell, which includes an electrode assembly as described above.

[0048] By applying the above electrode assembly to a battery cell, the cycle performance of the large jig of the battery cell can be improved.

[0049] An embodiment of the present application provides a battery, the battery including the battery cell described above.

[0050] An embodiment of the present application provides a power consuming device, the power consuming device including the above battery cell or the above battery. [Brief description of the drawings]

[0051] In order to more clearly explain the technical solutions in the embodiments of the present application or the prior art, the following briefly introduces drawings that need to be used in the embodiments or prior art description. It is obvious that the drawings in the following description are only some embodiments of the present application, and those skilled in the art can also obtain other drawings based on the structures shown in these drawings without exerting creative efforts. [Figure 1]1 is a flow chart of a method for making an adhesive according to an embodiment of the present application. [Diagram 2] 1 is a flow chart of a method for making an adhesive according to an embodiment of the present application. [Diagram 3] FIG. 2 is a schematic diagram of the core-shell structure of an adhesive according to an embodiment of the present application. [Figure 4] 1 is a scanning electron microscope view of an adhesive according to an embodiment of the present application. [Diagram 5] FIG. 2 is a schematic diagram of an electrode assembly according to an embodiment of the present application. [Figure 6] FIG. 6 is an exploded view of an electrode assembly according to the embodiment of the present application shown in FIG. 5. [Figure 7] FIG. 1 is a schematic diagram of a battery module according to an embodiment of the present application. [Figure 8] FIG. 1 is a schematic diagram of a battery pack according to an embodiment of the present application. [Figure 9] FIG. 9 is an exploded view of the battery pack according to the embodiment of the present application shown in FIG. 8. [Figure 10] BRIEF DESCRIPTION OF THE DRAWINGS Fig. 1 is a schematic diagram of a power consuming device according to an embodiment of the present application.The realization of the objects, functional features and advantages of the present application will be further explained with reference to the drawings in conjunction with the embodiments. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0052] The following clearly and completely describes the technical solutions in the embodiments of the present application in conjunction with the drawings in the embodiments of the present application, and obviously, the described embodiments are only some of the embodiments of the present application, not all of the embodiments. All other embodiments obtained based on the embodiments of the present application without the need for creative efforts by those skilled in the art are all within the scope of protection of the present application.

[0053] Hereinafter, with appropriate reference to the drawings, embodiments specifically disclosing an adhesive and a manufacturing method thereof, as well as a separator, an electrode assembly, a battery cell, a battery, and a power consumption device each including the adhesive will be described in detail. However, unnecessary detailed description may be omitted. For example, detailed description of well-known matters and duplicated description of structures that are actually the same may be omitted. This is to avoid the following description becoming unnecessarily long and to allow those skilled in the art to easily understand. Note that the drawings and the following description are provided to allow those skilled in the art to fully understand the present application, and are not intended to limit the subject matter described in the claims.

[0054] The "ranges" disclosed in this application are defined in the form of lower and upper limits, and a given range is defined by selecting one lower limit and one upper limit, and the selected lower and upper limits define the boundaries of the particular range. Such defined ranges may be inclusive or exclusive of the extreme values, and may be arbitrarily combined, i.e., any lower limit may be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a particular parameter, it is understood that ranges of 60-110 and 80-120 are also envisaged. However, if 1 and 2 are listed as minimum range values, and 3, 4, and 5 are listed as maximum range values, the ranges 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5 are all envisaged. In this application, unless otherwise specified, the numerical range "ab" represents a shorthand representation of any combination of real numbers from a to b, where a and b are both real numbers. For example, the numerical range "0-5" represents a list of all real numbers between "0-5" already listed in this specification, and "0-5" is just a shorthand representation of combinations of these numbers. Also, expressing a parameter as an integer ≧2 is equivalent to disclosing that the parameter is, for example, the integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0055] Unless otherwise stated, all the embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0056] Unless otherwise stated, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0057] Unless otherwise stated, all steps in this application may be performed in sequence or randomly, and preferably in sequence. For example, the method includes steps (a) and (b) to mean that the method may include steps (a) and (b) performed in sequence, or may include steps (b) and (a) performed in sequence. For example, the method mentioned above may further include step (c) to mean that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), may include steps (a), (c) and (b), may include steps (c), (a) and (b), etc.

[0058] Unless otherwise specified, the terms "comprise" and "comprises" referred to in this application may be open ended or closed ended. For example, the terms "comprise" and "comprises" may further include or include other ingredients not listed, or may include or include only the ingredients listed.

[0059] Unless otherwise stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, "A or B" is satisfied if A is true (or exists) and B is false (or does not exist), if A is false (or does not exist) but B is true (or exists), or if both A and B are true (or exist).

[0060] The battery core of the battery has an opening problem, that is, gaps easily form between the plates and the separator, which leads to poor battery cycling performance.

[0061] For example, polyvinylidene fluoride is the most commonly used adhesive and is widely used in separators, but at present, the price of polyvinylidene fluoride is rising rapidly and the market supply is tight. The problem of high temperature shrinkage of the separator can be partially solved by coating the surface of the lithium battery separator with polyvinylidene fluoride polymer, and cold pressing is performed after winding the battery core, but general polyvinylidene fluoride is a homopolymer with a crystallinity of about 50%, which means that the adhesive strength with the positive and negative electrodes is insufficient, and the opening problem of the battery core often occurs, which cannot meet the performance requirements of the coated separator of the power lithium-ion battery.

[0062] That is, the problem of high temperature shrinkage of the separator can be partially solved by coating the surface of the battery separator with polyvinylidene fluoride polymer, and cold pressing is performed after winding the battery core, but general polyvinylidene fluoride is a homopolymer with a crystallinity of about 50%, and the adhesive strength with the positive and negative electrodes is insufficient, so the opening problem of the battery core often occurs. The opening in the battery core forms a gap between the electrode plate and the separator, loosening the structure of the entire battery core, reducing the hardness of the battery core, and deteriorating the cycle performance of the battery core.

[0063] The battery core is formed by bonding the positive and negative electrode plates and the separator, and the battery core has a certain hardness, that is, the bonded positive and negative electrode plates and the separator are supported by adhering to each other to form a structure with a certain thickness, so the structure with a certain thickness has a certain hardness, and the negative electrode expands during charging and discharging. If the adhesive strength is weak, a gap is formed between the positive and negative electrode plates and the separator, and the positive and negative electrode plates and the separator cannot be supported by adhering to each other, and the battery core becomes loose and the hardness is reduced, and at this time, the power performance of the battery core is deteriorated, for example, the rate performance is reduced and the cycle performance is deteriorated. For example, in an electric vehicle, the battery core of the battery becomes loose, the charging speed of the battery is slowed and the cycle performance of the battery is deteriorated, which directly causes the battery life to be shortened, and the electric vehicle needs to replace the battery frequently, which increases the cost of the electric vehicle for consumers.

[0064] Based on this, the present application provides an adhesive, the adhesive comprising a core layer structure and a shell layer structure provided on a surface of the core layer structure, the shell layer structure comprising a polyacrylate-based polymer, and the core layer structure comprising a polyvinylidene fluoride polymer.

[0065] An adhesive is a material that has adhesive properties for bonding dissimilar substances together.

[0066] The core-shell structure consists of a central core and a shell covering the outer layer.

[0067] The core layer structure is a structure that is located inside the core-shell structure and is covered with an outer shell.

[0068] The shell layer structure is a structure that is located outside the core-shell structure and covers the surface of the core layer structure.

[0069] A polyacrylate-based polymer is a polymer having acrylate monomers.

[0070] Polyvinylidene fluoride polymers are polymers in which vinylidene fluoride is the monomer.

[0071] The present application achieves improving the crystallinity of the polyvinylidene fluoride polymer in the core-shell adhesive by coating the polyacrylate-based polymer to obtain a core-shell adhesive, thereby improving the adhesive performance of the core-shell adhesive, and the adhesive improves the adhesive strength between the separator and the electrode plate. The adhesive of the present application has good adhesive performance, does not separate the electrode plate and the separator during the expansion of the electrode plate, maintains good hardness of the battery core, and improves the dynamic performance and cycle performance of the battery core.

[0072] Theoretically, with an increase in crystallinity, the molecular chain arrangement is tight and orderly, the void ratio is low, the intermolecular interaction force is increased, and the segment movement is difficult. As a result, the yield stress, strength, modulus and hardness of the polymer are all improved, but the breaking elongation and impact toughness are reduced. Obviously, the crystallization makes the polymer hard and brittle, and the adhesive performance is also reduced.

[0073] In the present application, polyvinylidene fluoride polymer is coated with polyacrylate-based polymer, and compared with uncoated polyvinylidene fluoride, the core-shell structure adhesive of the present application has a lower crystallinity and improved adhesive performance, and the adhesive of the core-shell structure can be used to improve the adhesive strength between the separator and the electrode plate and avoid the problem of opening of the battery core. At the same time, the crystallinity is lowered, the molecular structure of the adhesive becomes more disordered, the porosity is increased, and the adhesive's wettability with liquid is improved. By coating the adhesive on the separator, the separator's wettability with the electrolyte is improved, which is favorable for improving the cycle performance of the battery.

[0074] In some embodiments, the shell layer structure includes a plurality of cases, the plurality of cases being spaced apart on a surface of the core layer structure.

[0075] As shown in Figures 3 and 4, the case made of polyacrylate polymer is not continuously coated on the surface of the core layer structure, but is attached to the surface of the core layer structure at intervals, resembling a raspberry-like structure. As can be seen, the shell layer structure is equivalent to being composed of a plurality of cases, and there are gaps between adjacent cases, and the surface of the core layer structure can be exposed at the gaps. In this way, the polyvinylidene fluoride polymer core layer structure is exposed, and the core layer structure has relatively good adhesion, so the core layer structure exposed between the cases can also reinforce the adhesion performance. In addition, the shell layer structure that discontinuously covers the core layer structure has a larger specific surface area than the shell layer structure that completely covers the core layer structure, and thus the surface structure with adhesive function can play a greater adhesive role.

[0076] As can be seen, no crosslinking reaction occurs between the functional groups on the surface of the polyvinylidene fluoride polymer core layer and the polyacrylate-based polymer shell layer, and the mechanism between the core layer and the shell layer is mainly ionic bonding, and the constituent monomers of the polyvinylidene fluoride polymer are adsorbed onto the constituent monomers of the polyacrylate-based polymer through the action of ionic bonds, van der Waals forces, etc.

[0077] In some embodiments, the weight ratio of the polyvinylidene fluoride polymer to the polyacrylate-based polymer is (2-100):1, optionally (10-80):1.

[0078] In order to obtain the above-mentioned core-shell structure of raspberry-like structure, the mass of polyvinylidene fluoride polymer is greater than the mass of polyacrylate-based polymer, and the mass of core layer structure is greater than the mass of shell layer structure, so that the surface of the core layer structure is not completely covered with the shell layer structure, so that some structure is exposed on the surface of the core layer structure, thereby obtaining the above-mentioned core-shell structure of raspberry-like structure. Here, the mass of the core layer structure is greater than the mass of the shell layer structure, and the mass ratio of the core layer structure to the shell layer structure can be (2 to 100): 1, and in the above (2 to 100): 1, the value includes the minimum and maximum values ​​of this range, and each value between such minimum and maximum values, and specific examples include, but are not limited to, the point values ​​in the examples and 2: 1, 10: 1, 20: 1, 30: 1, 40: 1, 50: 1, 60: 1, 70: 1, 80: 1, 90: 1, 100: 1, etc.

[0079] In some embodiments, the mass ratio of the core layer structure to the shell layer structure is (10-80):1.

[0080] In order to obtain the above-mentioned raspberry-shaped core-shell structure, the mass of the polyvinylidene fluoride polymer is greater than the mass of the polyacrylate-based polymer, and the mass of the core layer structure is greater than the mass of the shell layer structure, so that the surface of the core layer structure is not completely covered with the shell layer structure, so that some structure is exposed on the surface of the core layer structure, thereby obtaining the above-mentioned raspberry-shaped core-shell structure. Here, the mass of the core layer structure is greater than the mass of the shell layer structure, and the mass ratio of the core layer structure to the shell layer structure can be (10-80):1, and in the above (10-80):1, the value includes the minimum and maximum values ​​of this range, and each value between such minimum and maximum values, and specific examples include, but are not limited to, the point values ​​in the examples and 10:1, 20:1, 30:1, 40:1, 50:1, 60:1, 70:1, 80:1, etc.

[0081] In the mass ratio test method, when the mass of the monomer for producing the core layer structure, which is added during the reaction process in the manufacturing process of the adhesive, is recorded as m, and the mass of the monomer for producing the shell layer structure is recorded as n, the mass ratio of the core layer structure to the shell layer structure is m:n.

[0082] In some embodiments, the adhesive has a volume average particle size Dv50 of 0.5 μm-50 μm, optionally 7 μm-8 μm.

[0083] The volume average particle size Dv50 of the adhesive can be tested using methods known in the art, for example, see GB / T 19077-2016, characterization tests can be performed using Malvern Mastersizer, for example, using an instrument such as Malvern's Mastersizer-3000.

[0084] Theoretically, the volume average particle diameter Dv50 of the adhesive in the present application may be less than 0.5 μm or more than 50 μm. However, considering that the adhesive in the present application is used in a separator, the volume average particle diameter Dv50 of the adhesive cannot be too large or too small. If the adhesive is too small, it is likely to block the pores of the separator, reducing the permeability of lithium ions through the separator. If the adhesive is too large, a thick coating will be formed when the adhesive is applied to the separator. Since this affects the energy density of the battery produced later, the volume average particle diameter Dv50 of the adhesive is 0.5 μm-50 μm, and in the above 0.5 μm-50 μm, the value includes the minimum and maximum values ​​of this range, and each value between such minimum and maximum values. Specific examples include, but are not limited to, the point values ​​in the examples and 0.5 μm, 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, etc.

[0085] In some embodiments, the adhesive has a volume average particle size Dv50 of 7 μm-8 μm.

[0086] When the volume average particle diameter Dv50 of the adhesive is 7 μm-8 μm, the performance of the resulting separator is excellent, and in the above 7 μm-8 μm, the values ​​include the minimum and maximum values ​​of this range, and each value between such minimum and maximum values, and specific examples include, but are not limited to, the point values ​​in the examples and 7 μm, 7.5 μm, 8 μm, etc.

[0087] In some embodiments, the constituent monomers of the polyacrylate-based polymer include a first polymerizable flexible monomer, a second polymerizable polar monomer, and a third polymerizable molecular weight modifying monomer.

[0088] Regarding the flexible monomer, the homopolymer glass transition temperature of the flexible monomer is lower than the homopolymer glass transition temperature of the rigid monomer, and the flexible monomer has a certain flexibility relative to the rigid group, allowing the segment to move freely. The flexible monomer can adjust the glass transition temperature of the segment polymer and improve the toughness of the adhesive when applied, which contributes to exerting a good adhesive effect.

[0089] A polar monomer is a monomer that contains a polar group, and the polar monomer contributes to improving the adhesiveness of the polymer.

[0090] The molecular weight adjusting monomer is a monomer that is involved in a crosslinking reaction and is used to adjust the molecular weight of the polymer. The molecular weight of the adhesive within a certain range contributes to improving the adhesive properties.

[0091] The constituent monomers of the polyacrylate polymer in the present application include a first polymerizable flexible monomer, a second polymerizable polar monomer, and a third polymerizable molecular weight adjusting monomer. By crosslinking the three types of monomers to obtain a polymer, the molecular weight and glass transition temperature of the polymer can be controlled, thereby improving the adhesive performance of the adhesive.

[0092] The softening point of the modified polymer is lower than that of pure polyvinylidene fluoride-based polymer, and when the battery core is pre-cold pressed, the adhesive can fully penetrate into the gap between the positive and negative electrode plates and the separator, that is, there is a gap between the electrode plates and the separator, and the adhesive penetrates into the gap, effectively connecting the electrode plates and the separator, and the adhesive is not easily separated from the gap. During the expansion of the electrode plates, the adhesive has toughness, and can effectively connect the two even during expansion, allowing the adhesive to fully exert its adhesive performance, which further contributes to improving the dynamic performance of the battery and the cycle performance of the large jig.

[0093] Here, the softening point is the temperature at which a substance softens. It is related not only to the structure of a polymer but also to the size of its molecular weight. In the present application, the softening point of the polymer is improved by adjusting the molecular weight of the polymer with a third polymerization molecular weight adjusting monomer.

[0094] Here, the cycle performance of the large jig is a cycle functional test performance of a battery core. In the test process, a jig is attached to the battery core, and a certain force is applied to the jig to press the battery core. When the battery core is fully charged, expansion occurs, and the battery core is deformed due to the double pressure of the clamping force and expansion force of the jig. This test is used to test the shape retention performance and pressure resistance performance of the battery core. When the adhesive of the present solution is used, the adhesive performance is good, so the expansion of the battery core is weakened and the shape retention of the battery core is relatively good. The battery core using the adhesive of the present application has relatively good performance retention under the test conditions of the large jig, and the battery core obtained by using the adhesive of the present solution has excellent deformation retention. When the battery core is assembled to form a battery, the battery core is not easily deformed, so the space for installing the battery core in the battery can be saved, and thus the volume of the battery can be made smaller. Therefore, if the battery core is prone to deformation, it will press on the structure near the battery core; in order to avoid this phenomenon, a larger space is needed to accommodate the deformed battery core, that is, space in the battery needs to be reserved to accommodate the deformed part of the battery core, thereby occupying more space within the battery.

[0095] At the same time, it was explained that the good cycle performance of the large jig for the battery core also means that the cycle performance of the battery core is good. For example, if the battery core expands, the gap between the electrode plates and the separator becomes larger, the path through which lithium ions pass through the positive and negative electrodes becomes longer, and the cycle becomes worse.

[0096] In some embodiments, the molar ratio of the first polymerizable flexible monomer to the second polymerizable polar monomer to the third polymerizable molecular weight adjusting monomer is 1:(0.01-0.8):(0.01-0.15), optionally 1:(0.05-0.7):(0.05-0.12).

[0097] The molar ratio test method is to record the number of moles of each type of monomer used to produce the shell layer structure during the reaction process of the adhesive production, where the number of moles of each type of monomer is the mass of each type of monomer divided by the molecular weight of each type of monomer. The number of moles of the first polymerizable flexible monomer is defined as a, the number of moles of the second polymerizable polar monomer is defined as b, and the number of moles of the third polymerizable molecular weight adjusting monomer is defined as c, and the molar ratio of the first polymerizable flexible monomer, the second polymerizable polar monomer, and the third polymerizable molecular weight adjusting monomer is a:b:c.

[0098] When the molar ratio of the first polymerizable flexible monomer, the second polymerizable polar monomer, and the third polymerizable molecular weight adjusting monomer is 1:(0.01-0.8):(0.01-0.15), the adhesive has excellent adhesive effect, and may be, for example, 1:0.01:0.01, 1:0.1:0.01, 1:0.4:0.01, 1:0.8:0.01, 1:0.01:0.05, 1:0.01:0.1, 1:0.01:0.15, 1:0.1:0.01, 1:0.1:0.05, 1:0.1:0.15, 1:0.4:0.01, 1:0.4:0.05, 1:0.4:0.15, 1:0.8:0.01, 1:0.8:0.05, 1:0.8:0.15, etc., and is not specifically limited.

[0099] In some embodiments, the molar ratio of the first polymerizable flexible monomer to the second polymerizable polar monomer to the third polymerizable molecular weight adjusting monomer is 1:(0.05-0.7):(0.05-0.12).

[0100] When the molar ratio of the first polymerizable flexible monomer to the second polymerizable polar monomer to the third polymerizable molecular weight adjusting monomer is 1:(0.05-0.7):(0.05-0.12), the adhesive has excellent adhesion effect. In the above 1:(0.05-0.7):(0.05-0.12), the values ​​include the minimum and maximum values ​​of this range, and each value between such minimum and maximum values. Specific examples include, but are not limited to, the point values ​​in the examples and 1:0.05:0.05, 1:0.1:0.05, 1:0.4:0.05, 1:0.7:0.05, 1:0.1:0.05, 1:0.1:0.1, 1:0.1:0.12, etc.

[0101] In some embodiments, the structure of the first polymerizable flexible monomer contains an ester bond (-COOR, where R is typically another non-H group such as an alkyl group), the structure of the second polymerizable polar monomer contains a cyano group (-C3N), and the structure of the third polymerizable molecular weight adjusting monomer contains an amide bond (-CO-NH-).

[0102] The ester bond can improve the flexibility of the molecular chain, the cyano group can improve the polarity of the monomer, and the amide bond has polarity and is easy to form hydrogen bonds, which can improve the adhesiveness. The first polymerizable flexible monomer contains an ester bond in its structure, the second polymerizable polar monomer contains a cyano group in its structure, and the third polymerizable molecular weight adjusting monomer contains an amide bond, so that the polymer obtained by polymerizing the above three types of monomers can control the molecular weight and glass transition temperature of the polymer, thereby improving the adhesive performance of the adhesive.

[0103] In some embodiments, the first polymerizable flexible monomer is an acrylate based monomer, the second polymerizable polar monomer is an acrylonitrile based monomer, and the third polymerizable molecular weight adjusting monomer is an acrylamide based monomer.

[0104] The acrylate monomer can improve the swelling resistance of the polymer, and can adjust the glass transition temperature of the polymer as a flexible monomer segment in the molecular segment, thereby improving the toughness of the adhesive when applied, thereby contributing to the exertion of good adhesive action.

[0105] The acrylonitrile monomer has a cyano group with strong polarity, which contributes to improving the ion conductivity and the adhesiveness.

[0106] The acrylamide monomer not only serves to adjust the molecular weight, but also has relatively good adhesive properties.

[0107] The polymers produced by the above three kinds of monomers can control the molecular weight and glass transition temperature of the polymers, thereby improving the adhesive performance of the adhesive.

[0108] In some embodiments, the acrylate based monomers include at least one of methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, n-propyl acrylate, cyclohexyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, isobornyl methacrylate, lauryl methacrylate, 2-hydroxyethyl methacrylate, and 2-hydroxypropyl methacrylate; and / or the acrylonitrile based monomers include at least one of acrylonitrile and methacrylonitrile; and / or the acrylamide based monomers include at least one of acrylamide, N-methylol acrylamide, and N-butoxymethacrylamide.

[0109] The acrylate monomer contributes to improving the adhesive properties of the adhesive. The acrylate monomer may include at least one of methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, n-propyl acrylate, cyclohexyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, isobornyl methacrylate, lauryl methacrylate, 2-hydroxyethyl methacrylate, and 2-hydroxypropyl methacrylate. In other words, the constituent monomers of the polyacrylate polymer may include one of the above acrylate monomers, or may include multiple acrylate monomers, and are not specifically limited.

[0110] The acrylonitrile-based monomer contributes to improving the adhesive properties of the adhesive, and the acrylonitrile-based monomer includes at least one of acrylonitrile and methacrylonitrile. In other words, the constituent monomers of the polyacrylate-based polymer may include one of the above acrylonitrile-based monomers or may include multiple of the above acrylonitrile-based monomers, and are not specifically limited.

[0111] The acrylamide monomer contributes to improving the adhesive properties of the adhesive, and the acrylamide monomer includes at least one of acrylamide, N-methylolacrylamide, and N-butoxymethacrylamide. In other words, the constituent monomers of the polyacrylate polymer may include one of the above acrylamide monomers or may include multiple acrylamide monomers, and are not specifically limited.

[0112] In some embodiments, the polyvinylidene fluoride polymer comprises at least one of vinylidene fluoride polymer, vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-pentafluoropropylene copolymer, vinylidene fluoride-tetrafluoropropylene copolymer, vinylidene fluoride-trifluoropropylene copolymer, vinylidene fluoride-perfluorobutene copolymer, vinylidene fluoride-tetrafluoroethylene copolymer, vinylidene fluoride-trifluoroethylene copolymer, vinylidene fluoride-trifluorochloroethylene copolymer, or vinylidene fluoride-vinyl fluoride copolymer.

[0113] In addition to having good chemical resistance and corrosion resistance, polyvinylidene fluoride polymers also have special properties such as high temperature resistance, oxidation resistance, weather resistance, and radiation resistance, as well as piezoelectric, dielectric, and thermoelectric properties, and are often used in lithium-ion battery separators.

[0114] The polyvinylidene fluoride polymer used in the present application includes at least one of vinylidene fluoride polymer, vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-pentafluoropropylene copolymer, vinylidene fluoride-tetrafluoropropylene copolymer, vinylidene fluoride-trifluoropropylene copolymer, vinylidene fluoride-perfluorobutene copolymer, vinylidene fluoride-tetrafluoroethylene copolymer, vinylidene fluoride-trifluoroethylene copolymer, vinylidene fluoride-trifluorochloroethylene copolymer, or vinylidene fluoride-vinyl fluoride copolymer, i.e., the polyvinylidene fluoride polymer may include one of the above polyvinylidene fluoride polymers, or may include a plurality of the above polyvinylidene fluoride polymers, and is not specifically limited.

[0115] As shown in FIG. 1 , the present application further provides a method for producing an adhesive, Add water, an emulsifier, an initiator, and constituent monomers of polyvinylidene fluoride polymer into a reaction vessel, stir, and heat under reaction pressure to polymerize, thereby obtaining a seed emulsion, which is kept as a reserve; mixing and stirring water, an emulsifier, and a constituent monomer of a polyacrylate-based polymer to obtain a shell layer monomer pre-emulsion, which is used as a reserve; The shell layer monomer pre-emulsion, initiator and water are added to the seed emulsion, and the mixture is stirred and heated to react with each other to obtain a core-shell structured adhesive.

[0116] In the present application, a seed emulsion of polyvinylidene fluoride polymer for the core layer is first obtained by emulsion polymerization, and then a polyacrylate-based polymer for the shell layer is prepared on the surface of the core layer structure by emulsion polymerization, and finally an adhesive having a core-shell structure is formed.

[0117] Regarding emulsion polymerization, emulsion polymerization is a process in which a monomer is dispersed in water with an emulsifier by mechanical stirring to form an emulsion, and an initiator is added to start the monomer polymerization.

[0118] The core-shell structure consists of a central core and a shell covering the outer layer.

[0119] The seed emulsion is prepared by first preparing a seed latex from a small amount of monomers by a general emulsion polymerization method, and then adding a small amount of the seed latex to a proper emulsion polymerization recipe, and using the seed emulsion latex particles as the core, the polymerization reaction is carried out, and the latex particles are continuously grown.

[0120] A pre-emulsion is a solution obtained by pre-emulsifying a monomer, and emulsification is a process in which a liquid is uniformly dispersed in another liquid with which it is incompatible as extremely small droplets, and water, an emulsifier, and the constituent monomers of the polyacrylate polymer are mixed and stirred, and the constituent monomers of the polyacrylate polymer are dispersed in water by the action of the emulsifier.

[0121] About emulsifiers: Emulsifiers are substances that can convert incompatible oils and water into emulsions that are less likely to stratify. Emulsifiers are generally surface active agents that combine the properties of both hydrophilic polar groups and hydrophobic (lipophilic) non-polar groups.

[0122] Regarding initiators, initiators are substances capable of initiating the polymerization reaction of monomers. For example, radical initiators are compounds that are easily decomposed into radicals (i.e., primary radicals) by heat and may be used to initiate the radical polymerization and copolymerization reactions of ene and diene monomers.

[0123] For convenience of description, in the above adhesive manufacturing method, the process of the manufacturing method is divided into step 1, step 2, and step 3 according to the order of the described paragraphs. As can be understood by a person skilled in the art, in the above method of specific embodiments, the described order of each step does not mean a strict execution order and does not constitute any limitation on the implementation process, and the specific execution order of each step should be determined according to its function and possible inherent logic.

[0124] In step 1, water, emulsifier, initiator, and constituent monomers of polyvinylidene fluoride polymer are mixed and stirred, and the water and emulsifier are stirred and dispersed to form an emulsion, that is, the emulsifier forms micelles in the water phase, and the monomers are solubilized in most of the micelles, and the monomers enter the reaction system of the micelles at a certain pressure, and under the condition of increasing temperature, the initiator starts the polymerization of the monomers inside the micelles to obtain a core layer seed emulsion; in step 2, water, emulsifier, and constituent monomers of polyacrylate polymer are mixed and stirred, and the emulsifier and water are similarly dispersed to form an emulsion, and the constituent monomers of polyacrylate polymer enter the micelles to obtain a shell layer monomer pre-emulsion, and the pre-emulsion is then formed. In step 3, the initiator, water, and the shell layer monomer pre-emulsion obtained in step 2 are added to the seed emulsion obtained in step 1, and are stirred and heated to react, so that the constituent monomers of the polyacrylate polymer form polymers on the surface of the core layer, and the polyacrylate polymer adheres to the surface of the core layer structure of the polyvinylidene fluoride polymer, thereby obtaining a core-shell structure adhesive; in step 1, the dispersion polymerization and core formation mechanism of polyvinylidene fluoride belongs to the oligomer core formation mechanism; at the same conversion rate, the particle size of the polyvinylidene fluoride latex particles can be made smaller by increasing the content of the initiator or emulsifier.

[0125] In step 1, since the constituent monomers of the polyvinylidene fluoride polymer are in a gaseous state and do not easily enter micelles at normal pressure, the gaseous monomers are introduced into the micelles by pressurization to efficiently proceed with the reaction.

[0126] Both steps 1 and 3 are carried out under heating conditions because a certain temperature is required for the initiator in step 1 and step 3 to be converted to have the function of initiating monomer polymerization.

[0127] At the same time, the mass of water in step 3 being equal to or greater than 0 means that water may or may not be added in step 3; it can be understood that if enough water is added in steps 1 and 2, that is, if the water added in steps 1 and 2 can make the solid content after the reaction in steps 1, 2 and 3 fall within a preset range, then water may not be added in step 3; if not enough water is added in steps 1 and 2, a certain amount of water needs to be added in step 3 to adjust the solid content of the system, so as to prevent the viscosity after the reaction from becoming too large and the reaction rate from slowing down.

[0128] As can be understood, the stirring rate in step 1, step 2 and step 3 is 1000 r / min-5000 r / min, for example, it can be 1000 r / min, 2000 r / min, 3000 r / min, 4000 r / min, 5000 r / min, etc., not specifically limited, and the stirring time can be 60 min ± 20 min. Under this stirring condition, a uniformly emulsified prepolymer is obtained and reserved.

[0129] In some embodiments, the ratio of the constituent monomer mass of the polyvinylidene fluoride polymer to the constituent monomer mass of the polyacrylate polymer is (2-100):1, and optionally (10-80):1.

[0130] In order to obtain the above-mentioned raspberry-shaped core-shell structure, the mass of the core layer structure is made larger than the mass of the shell layer structure, so that the surface of the core layer structure is not completely covered with the shell layer structure, so that a part of the structure is exposed on the surface of the core layer structure, thereby obtaining the above-mentioned raspberry-shaped core-shell structure. Here, the mass of the core layer structure is larger than the mass of the shell layer structure, and the mass ratio of the core layer structure to the shell layer structure may be (2 to 100): 1, for example, 2: 1, 10: 1, 20: 1, 30: 1, 40: 1, 50: 1, 60: 1, 70: 1, 80: 1, 90: 1, 100: 1, etc., and is not specifically limited.

[0131] In some embodiments, the step of adding water, an emulsifier, an initiator, and constituent monomers of polyvinylidene fluoride polymer to a reaction vessel, stirring, and heating at reaction pressure to polymerize to obtain and reserve a seed emulsion includes the steps of removing oxygen gas from the reaction vessel, adding water, an emulsifier, an initiator, and constituent monomers of polyvinylidene fluoride polymer to a reaction vessel, stirring, and heating to 75±10°C at reaction pressure to polymerize to obtain and reserve a seed emulsion.

[0132] Considering that oxygen gas acts as a polymerization inhibitor and affects the polymerization reaction during polymerization, it is necessary to remove the oxygen gas from the reaction vessel. For example, before performing step 1, the oxygen gas from the reaction vessel may be removed. For example, nitrogen gas may be introduced into the reaction vessel to replace the oxygen gas. After the oxygen gas is removed, water, an emulsifier, an initiator, and constituent monomers of the polyvinylidene fluoride polymer are further added to the reaction vessel, stirred, heated to 75±10°C under reaction pressure, and a polymerization reaction is carried out to obtain a seed emulsion, which may be kept as a reserve.

[0133] In some embodiments, the steps of removing oxygen gas from the reaction vessel, charging water, an emulsifier, an initiator, and constituent monomers of the polyvinylidene fluoride polymer into the reaction vessel, stirring, raising the temperature to 75±10°C under reaction pressure, performing a polymerization reaction, obtaining a seed emulsion, and preserving the seed emulsion include the steps of charging water, an emulsifier, and an initiator into the reaction vessel, stirring, removing oxygen gas from the reaction vessel, and further charging constituent monomers of the polyvinylidene fluoride polymer into the reaction vessel, stirring, raising the temperature to 75±10°C under reaction pressure, performing a polymerization reaction, obtaining a seed emulsion, and preserving the seed emulsion.

[0134] Considering that the monomer emulsification can be more fully achieved by first adding water, an emulsifier and an initiator to a reaction vessel, stirring, and then adding the constituent monomers of the polyvinylidene fluoride polymer, the step of producing a seed emulsion may also be a step of adding water, an emulsifier and an initiator to a reaction vessel, stirring, removing oxygen gas from the reaction vessel, and then adding the constituent monomers of the polyvinylidene fluoride polymer to the reaction vessel, raising the temperature to 75±10°C under reaction pressure, carrying out a polymerization reaction, obtaining a seed emulsion and keeping it as a reserve.

[0135] In some embodiments, the steps of removing oxygen gas from the reaction vessel, introducing water, an emulsifier, an initiator, and constituent monomers of polyvinylidene fluoride polymer into the reaction vessel, stirring, heating to 75±10°C under reaction pressure, conducting a polymerization reaction, obtaining a seed emulsion and setting aside as a reserve include the steps of removing oxygen gas from the reaction vessel, introducing water, an emulsifier, an initiator, and constituent monomers of polyvinylidene fluoride polymer into the reaction vessel, controlling the reaction pressure in the reaction vessel to 3.0MP to 4MP, stirring, heating to 75±10°C, conducting a polymerization reaction, and when the pressure in the reaction vessel drops to 3.0MP, continuing to introduce constituent monomers of polyvinylidene fluoride polymer and controlling the pressure in the reaction vessel to 3.0MP to 4MP, obtaining a seed emulsion and setting aside as a reserve until the reaction is completed.

[0136] Considering that the constituent monomer of polyvinylidene fluoride polymer is gas, in the process of polymerization reaction, the monomer in the reaction vessel is constantly consumed, and the pressure in the reaction vessel is constantly decreasing. When the pressure decreases to a certain value, it is difficult for the monomer to enter the solution system and reach the micelle to react, so it is necessary to control the pressure in the reaction vessel to a certain range value to ensure that the monomer can effectively participate in the reaction. Therefore, the step of producing seed emulsion may be the step of removing oxygen gas in the reaction vessel, adding water, emulsifier, initiator, and constituent monomer of polyvinylidene fluoride polymer to the reaction vessel, controlling the reaction pressure in the reaction vessel to 3.0MP-4MP, stirring, raising the temperature to 75±10℃, carrying out polymerization reaction, when the pressure in the reaction vessel decreases to 3.0MP, continuing to add the constituent monomer of polyvinylidene fluoride polymer, controlling the pressure in the reaction vessel to 3.0MP-4MP, obtaining seed emulsion and keeping it as a reserve until the reaction is completed.

[0137] Considering that if the pressure is too low, the reaction rate will be slow, and if the pressure is too high, energy consumption will be high and the reaction will be violent, the control range of the reaction pressure is 3.0 MP to 4 MP, for example, 3.0 MP, 3.5 MP, 4 MP, etc., and is not specifically limited.

[0138] In some embodiments, the step of adding the shell layer monomer pre-emulsion, initiator and water to the seed emulsion, stirring and heating to react and obtain the adhesive includes the steps of adding water to the seed emulsion, stirring, adding the shell layer monomer pre-emulsion and initiator to the seed emulsion at a rate of 10 ml / min to 500 ml / min, heating to 90°C±10°C, and stirring for 30 min±20 min to react and obtain the adhesive.

[0139] In order to avoid the shell layer monomer pre-emulsion and the initiator being charged into the reaction vessel together to cause explosive polymerization, the shell layer monomer pre-emulsion and the initiator are charged into the reaction vessel at a certain drip rate, and the drip rate can be 10ml / min, 50ml / min, 100ml / min, 150ml / min, 200ml / min, 250ml / min, 300ml / min, 350ml / min, 400ml / min, 450ml / min, 500ml / min, etc., and is not specifically limited. At the same time, in order to effectively proceed with the reaction, the reaction is heated to 90℃±10℃ during the reaction to make the initiator start the polymerization reaction, and the reaction is stirred for 30min±20min to obtain the adhesive.

[0140] In some embodiments, the step of adding water to the seed emulsion, stirring, adding the shell layer monomer pre-emulsion and the initiator to the seed emulsion at a rate of 10 ml / min to 500 ml / min, heating to 90°C±10°C, stirring for 30 min±20 min to react, and obtaining an adhesive includes the steps of adding water to the seed emulsion, stirring, adding the shell layer monomer pre-emulsion and the initiator to the seed emulsion at a rate of 10 ml / min to 500 ml / min, heating to 90°C±10°C, stirring for 30 min±20 min to react, lowering the temperature, and adjusting the pH to 6 to 8 to obtain an adhesive.

[0141] The core-shell adhesive obtained by the production is prone to particle aggregation and deposition, which is disadvantageous for the use and storage of the adhesive. Therefore, in order to avoid the aggregation and precipitation of the core-shell adhesive, a pH adjusting agent is added to the produced adhesive, so that the core-shell particles are uniformly dispersed and the system is stabilized. The pH range of the adhesive is pH 6-8, and may be, for example, pH 6, pH 7, pH 8, etc., and is not specifically limited. As can be understood, the present application does not limit the specific pH adjusting agent to be adopted, and the pH may be adjusted using, for example, ammonia water.

[0142] In some embodiments, in step 1, the mass of the emulsifier is 0.1% to 5% of the mass of the constituent monomers of the polyvinylidene fluoride polymer, and the mass of the initiator is 0.15% to 1% of the mass of the constituent monomers of the polyvinylidene fluoride polymer.

[0143] The amount of emulsifier used must be moderate. The emulsifier is an important component of emulsion polymerization, and can convert incompatible oil (monomer)-water into a fairly stable emulsion that is not prone to stratification. In emulsion polymerization systems, the emulsifier has three main functions: the first is to reduce surface tension and disperse the monomer as fine droplets; the second is to form a protective layer on the droplet or colloidal particle surface to prevent aggregation and keep the emulsion stable; and the third is to form micelles and solubilize the monomer. The size and number of micelles depend on the amount of emulsifier used, so the amount of emulsifier used directly affects the performance of the product. In step 1, the mass of the emulsifier is 0.1% to 5% of the constituent monomer mass of the polyvinylidene fluoride polymer, and may be, for example, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 5%, etc., and is not specifically limited. The amount of initiator used has a significant effect on the polymerization rate and the performance of the product. If the amount of initiator used is increased, the polymerization rate becomes faster, the polymerization reaction becomes unstable, the molecular weight and yield decrease, and the performance of the polymer also deteriorates. In addition, if the amount of initiator is insufficient, the polymerization reaction becomes difficult. Therefore, in step 1, the mass of the initiator is 0.15% to 1% of the mass of the constituent monomers of the polyvinylidene fluoride polymer, and may be, for example, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95%, 1%, etc., and is not specifically limited.

[0144] In some embodiments, in step 1, the emulsifier comprises a polyfluoro compound and the initiator comprises an organic peroxide initiator, an inorganic peroxide initiator.

[0145] An emulsifier is a material that can make water into an emulsion state, and the specific type and structure of the emulsifier are not limited in this application, and any material that can perform the above function and does not affect the reaction system can be applied to this application, for example, in step 1, the emulsifier used includes a polyfluoro compound. An initiator is a material that can initiate the polymerization reaction of a monomer, and the specific type and structure of the initiator are not limited in this application, and any material that can perform the above function and does not affect the reaction system can be applied to this application, for example, in step 1, the initiator includes an organic peroxide initiator and an inorganic peroxide initiator, and the initiator used is preferably an organic peroxide initiator, and the prepared polyvinylidene fluoride has high stability.

[0146] In some embodiments, in step 1, the emulsifier comprises at least one of ammonium perfluoropolyether carboxylate, sodium perfluoropolyether carboxylate, or potassium perfluoropolyether carboxylate, and the initiator comprises at least one of benzoyl peroxide, di-tert-butyl peroxide, diisopropyl peroxydicarbonate, di-n-propyl peroxydicarbonate, diethyl peroxydicarbonate, and persulfates.

[0147] The emulsifier is a substance that can form water into an emulsion state, for example, the emulsifier used in step 1 includes at least one of ammonium perfluoropolyether carboxylate, sodium perfluoropolyether carboxylate, and potassium perfluoropolyether carboxylate, i.e., the emulsifier used can be one of the above, for example, sodium perfluoropolyether carboxylate, the emulsifier can reduce the surface tension between droplets and prevent the aggregation of monomer liquid or latex particles, and at the same time, the emulsifier can be a mixture of multiple substances among the above. The initiator is a substance that can start the polymerization reaction of the monomer, for example, the initiator used in step 1 includes at least one of benzoyl peroxide, di-tert-butyl peroxide, diisopropyl peroxydicarbonate, di-normal propyl peroxydicarbonate, diethyl peroxydicarbonate, and persulfate, i.e., the initiator used can be one of the above, for example, preferably, the initiator is diisopropyl peroxydicarbonate, and can be a mixture of multiple substances among the above.

[0148] In some embodiments, the constituent monomers of the polyvinylidene fluoride polymer include vinylidene fluoride, or the constituent monomers of the polyvinylidene fluoride polymer include at least one of vinylidene fluoride, vinylidene fluoride, hexafluoropropylene, pentafluoropropylene, tetrafluoropropylene, trifluoropropylene, perfluorobutene, tetrafluoroethylene, trifluoroethylene, trifluorochloroethylene, and vinyl fluoride.

[0149] A polyvinylidene fluoride polymer is a polymer having vinylidene fluoride as a monomer, and the monomer of the polyvinylidene fluoride polymer further includes at least one of hexafluoropropylene, pentafluoropropylene, tetrafluoropropylene, trifluoropropylene, perfluorobutene, tetrafluoroethylene, trifluoroethylene, trifluorochloroethylene, and vinyl fluoride in addition to vinylidene fluoride. That is, the polyvinylidene fluoride polymer may be a homopolymer of vinylidene fluoride or a copolymer of vinylidene fluoride and another fluorine-containing ethylene, and is not specifically limited.

[0150] In some embodiments, in step 1, water, an emulsifier, an initiator, and constituent monomers of a polyvinylidene fluoride polymer are added to a reaction vessel, stirred, and heated at a reaction pressure to polymerize, and a seed emulsion is obtained and prepared as a reserve, comprising the steps of adding water, a chain transfer agent, an emulsifier, an initiator, and constituent monomers of a polyvinylidene fluoride polymer to a reaction vessel, stirred, and heated at a reaction pressure to polymerize, and a seed emulsion is prepared as a reserve.

[0151] Chain transfer agents play a role in controlling the molecular weight distribution of the product in a polymerization reaction. Chain transfer is the process in which the active center in a chain polymerization reaction moves from the growing chain to another molecule. The number of active centers does not change, and the growing polymer chain loses activity, forming a stable polymer and reducing the molecular weight of the product.

[0152] In order to effectively control the molecular weight of the reaction product, in step 1, water, chain transfer agent, emulsifier, initiator, and constituent monomers of polyvinylidene fluoride polymer are added to a reaction vessel, stirred, and heated under reaction pressure to polymerize, to obtain a seed emulsion, which is reserved. During the polymerization reaction, a chain transfer agent is added to produce a seed emulsion for obtaining a polyvinylidene fluoride polymer with an appropriate molecular weight.

[0153] In some embodiments, the mass of the chain transfer agent is 1% to 3% of the mass of the constituent monomers of the polyvinylidene fluoride polymer, and the chain transfer agent includes an alcohol-based compound, an ester-based compound, a ketone-based compound, and a halogenated alkane.

[0154] The mass of the chain transfer agent is 1% to 3% of the mass of the constituent monomers of the polyvinylidene fluoride polymer, and may be, for example, 1%, 1.5%, 2%, 2.5%, 3%, etc., and is not specifically limited. The chain transfer agent includes an alcohol-based compound, an ester-based compound, a ketone-based compound, and a halogenated alkane, and the specific type of the chain transfer agent is not specifically limited.

[0155] In some embodiments, in step 2, the mass of the emulsifier is 0.15% to 5% of the mass of the constituent monomers of the polyacrylate-based polymer, and in step 3, the mass of the initiator is 0.15% to 1% of the mass of the constituent monomers of the polyacrylate-based polymer.

[0156] The amount of emulsifier used must be moderate. The emulsifier is an important component of emulsion polymerization, and can convert incompatible oil (monomer)-water into a fairly stable emulsion that is not prone to stratification. In emulsion polymerization systems, the emulsifier has three main functions: the first is to reduce surface tension and disperse the monomer as fine droplets; the second is to form a protective layer on the droplet or colloid particle surface to prevent aggregation and keep the emulsion stable; and the third is to form micelles and solubilize the monomer. The size and number of micelles depend on the amount of emulsifier used, so the amount of emulsifier used directly affects the performance of the product. In step 2, the mass of the emulsifier is 0.15% to 5% of the constituent monomer mass of the polyacrylate polymer, and may be, for example, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 5%, etc., and is not specifically limited. The amount of initiator used has a large effect on the polymerization rate and the performance of the product. If the amount of initiator used is increased, the polymerization rate will be faster, the polymerization reaction will become unstable, the molecular weight and yield will decrease, and the performance of the polymer will also deteriorate. In addition, if the amount of initiator is insufficient, the polymerization reaction will become difficult. Therefore, in step 3, the mass of the initiator is 0.15% to 1% of the mass of the constituent monomers of the polyacrylate polymer, and may be, for example, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95%, 1%, etc., and is not specifically limited.

[0157] In some embodiments, in step 2, the emulsifier comprises an anionic emulsifier, and in step 3, the initiator comprises an azo initiator, an organic peroxide initiator, or an inorganic peroxide initiator.

[0158] Anionic emulsifiers are surface active materials whose active moieties tend to dissociate into negative ions when dissolved in water, and are characterized by having one large organic anion and being able to react with bases to form salts. Depending on the structure of the negative ion-carrying moiety, they are divided into three types: carboxylate, sulfonate, and sulfate.

[0159] Regarding the azo-based initiator, the azo-based initiator is a radical initiator whose molecular structure contains a nitrogen-nitrogen double bond.

[0160] Peroxide initiators are compounds that contain a peroxy group (-OO-), and when exposed to heat, the -OO- bond is broken and split into two corresponding radicals, thereby initiating monomer polymerization. They are called peroxide initiators. There are two types: inorganic peroxides and organic peroxides. Inorganic peroxide initiators include hydrogen peroxide, ammonium persulfate, potassium persulfate, etc., while organic peroxide initiators include benzoyl peroxide, benzoyl t-butyl peroxide, methyl ethyl ketone peroxide, etc.

[0161] An emulsifier is a material that can make water form an emulsion state, and the specific type and structure of the emulsifier are not limited in this application, and any material that can perform the above function and does not affect the reaction system can be applied to this application, for example, in step 2, the emulsifier used includes an anionic emulsifier. An initiator is a material that can initiate the polymerization reaction of a monomer, and the specific type and structure of the initiator are not limited in this application, and any material that can perform the above function and does not affect the reaction system can be applied to this application, for example, in step 3, the initiator includes an azo initiator, an organic peroxide initiator, and an inorganic peroxide initiator.

[0162] In some embodiments, in step 2, the emulsifier comprises at least one of sodium dodecyl sulfate, sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, sodium styrene sulfonate, and sodium vinyl sulfonate, and in step 3, the initiator comprises at least one of azobisisobutyronitrile, azobisisoheptanonitrile, cumene hydroperoxide, tert-butyl hydroperoxide, benzoyl peroxide, ammonium persulfate, potassium persulfate, sodium persulfate, and hydrogen peroxide.

[0163] The emulsifier is a substance capable of forming water into an emulsion state, and for example, the emulsifier used in step 2 includes at least one of sodium dodecyl sulfate, sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, sodium styrene sulfonate, and sodium vinyl sulfonate, i.e., the emulsifier used may be one of the above, and for example, preferably, the emulsifier is sodium dodecylbenzene sulfonate, and may be a mixture of two or more of the above. The initiator is a substance capable of initiating the polymerization reaction of a monomer, and for example, the initiator used in step 3 includes at least one of azobisisobutyronitrile, azobisisoheptanonitrile, cumene hydroperoxide, tert-butyl hydroperoxide, benzoyl peroxide, ammonium persulfate, potassium persulfate, sodium persulfate, and hydrogen peroxide, i.e., the initiator used may be one of the above, and for example, preferably, the initiator is potassium persulfate, and may be a mixture of two or more of the above.

[0164] In some embodiments, the combined mass of water in step 1, water in step 2, and water in step 3 comprises 45%-60% of the mass of all materials in steps 1, 2, and 3, and the water in steps 1, 2, and 3 is deionized water.

[0165] Water, as a dispersion medium, has the functions of mass transfer and temperature control, etc., if the amount of water used is too little or too much, it is difficult to control the viscosity of the reaction system within a reasonable range, and the total mass of water in step 1, water in step 2 and water in step 3 accounts for 45%-60% of the mass of all materials in step 1, step 2 and step 3, for example, it can be 45%, 50%, 55%, 60%, etc., but is not specifically limited. At the same time, the water in step 1, step 2 and step 3 is deionized water, to avoid impurities in water affecting the polymerization reaction.

[0166] The embodiments of the present application further provide a separator, which includes the above adhesive or an adhesive obtained by the above adhesive manufacturing method. Since the adhesive employs all the technical solutions of all the embodiments, it has at least all the beneficial effects of the technical solutions of the embodiments, and will not be further described here.

[0167] The separator is coated with the above adhesive, which can improve the adhesive performance between the electrode plate and the adhesive and improve the opening problem in the conventional battery core pre-cold pressing process.

[0168] The embodiments of the present application further provide an electrode assembly, which includes the above separator. The separator adopts all the technical solutions of all the above embodiments, and therefore has at least all the beneficial effects of the technical solutions of the above embodiments, and will not be further described here.

[0169] The electrode assembly includes a positive electrode plate, a negative electrode plate, and a separator, and the adhesive is coated on the separator, thereby bonding the electrode plate and the separator together and improving the problem of openings between the electrode plate and the separator.

[0170] The embodiments of the present application further provide a battery cell, the battery cell including the above-mentioned electrode assembly, since the electrode assembly adopts all the technical solutions of all the above-mentioned embodiments, it has at least all the beneficial effects of the technical solutions of the above-mentioned embodiments, and will not be further described here.

[0171] By applying the above electrode assembly to a battery cell, the cycle performance of the large jig of the battery cell can be improved.

[0172] The embodiments of the present application further provide a battery, which includes the above-mentioned battery cell. The battery cell adopts all the technical solutions of all the above-mentioned embodiments, and therefore has at least all the beneficial effects of the technical solutions of the above-mentioned embodiments, and will not be further described herein.

[0173] The battery includes a battery module and a battery pack.

[0174] The embodiments of the present application further provide a power consumption device, which includes the above battery cell or the above battery, and the battery cell or the battery adopts all the technical solutions of all the above embodiments, and thus has at least all the beneficial effects of the technical solutions of the above embodiments, which will not be further described herein.

[0175] The electrode assembly, battery cell, battery and power consuming device of the present application will be described below with appropriate reference to the drawings.

[0176] In one embodiment of the present application, an electrode assembly is provided.

[0177] In general, the electrode assembly includes a positive electrode plate, a negative electrode plate, an electrolyte, and a separator. During charging and discharging of the battery, active ions shuttle between the positive electrode plate and the negative electrode plate to be absorbed and released. The electrolyte serves to conduct ions between the positive electrode plate and the negative electrode plate. The separator is disposed between the positive electrode plate and the negative electrode plate, and serves mainly to prevent short circuiting of the positive and negative electrodes, while allowing ions to pass through. The separator is the above-mentioned improved separator of the present application.

[0178] The positive electrode plate includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector.

[0179] For example, the positive electrode current collector has two opposing surfaces in the thickness direction of the positive electrode current collector, and the positive electrode film layer is disposed on either one or both of the two opposing surfaces of the positive electrode current collector.

[0180] In some embodiments, the positive electrode current collector may be a metal foil sheet or a composite current collector. For example, an aluminum foil may be used as the metal foil sheet. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base layer. The composite current collector may be formed by forming a metal material (such as aluminum, aluminum alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0181] In some embodiments, when the electrode assembly is a lithium ion battery, the positive electrode active material may adopt a positive electrode active material used in lithium ion batteries known in the art. For example, the positive electrode active material may include at least one material selected from the group consisting of lithium-containing phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, the present application is not limited to these materials, and other conventional materials that can be used as positive electrode active materials in batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Here, examples of the lithium transition metal oxide include lithium cobalt oxide (e.g., LiCoO2), lithium nickel oxide (e.g., LiNiO2), lithium manganese oxide (e.g., LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (e.g., LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM 333 (may be abbreviated as LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM 523 (may be abbreviated as LiNi 0.5 Co 0.25 Mn 0.25 O2(NCM 211 (may be abbreviated as LiNi 0.6 Co0.2 Mn 0.2 O2(NCM 622 (may be abbreviated as LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM 811 Lithium nickel cobalt aluminum oxide (e.g., LiNi 0.85 Co 0.15 Al 0.05 Examples of the lithium-containing phosphate having an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (e.g., LiFePO4 (which may be abbreviated as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (e.g., LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium manganese iron phosphate, and a composite material of lithium manganese iron phosphate and carbon.

[0182] In some embodiments, the positive electrode membrane layer further optionally includes an adhesive. For example, the adhesive may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0183] In some embodiments, the positive electrode membrane layer further optionally includes a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers, by way of example.

[0184] In some embodiments, the positive electrode plate can be manufactured in the following manner: The components for manufacturing the positive electrode plate, such as the positive electrode active material, the conductive agent, the adhesive, and any other components, are dispersed in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry, which is then coated on a positive electrode current collector, and the positive electrode plate is obtained after processes such as drying and cold pressing.

[0185] The negative electrode plate includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, the negative electrode film layer including a negative electrode active material.

[0186] For example, the negative electrode current collector has two opposing surfaces in the thickness direction of the negative electrode current collector, and the negative electrode film layer is disposed on either one or both of the two opposing surfaces of the negative electrode current collector.

[0187] In some embodiments, the negative electrode current collector may be a metal foil sheet or a composite current collector. For example, the metal foil sheet may be a copper foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (such as copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0188] In some embodiments, the negative electrode active material may be a negative electrode active material for batteries known in the art. For example, the negative electrode active material may include at least one of artificial graphite, natural graphite, soft carbon, hard carbon, silicone-based materials, tin-based materials, and lithium titanate. The silicone-based material may be selected from at least one of silicon, silicone oxide, silicone carbon composite, silicone nitrogen composite, and silicone alloy. The tin-based material may be selected from at least one of tin, tin oxide, and tin alloy. However, the present application is not limited to these materials, and other conventional materials that can be used as a battery negative electrode active material may be used. These negative electrode active materials may be used alone or in combination of two or more.

[0189] In some embodiments, the negative electrode membrane layer further optionally comprises an adhesive, which may be selected from at least one of styrene butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0190] In some embodiments, the negative electrode film layer further optionally comprises a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0191] In some embodiments, the negative electrode membrane layer optionally further comprises other auxiliary agents, such as a thickening agent (eg, sodium carboxymethylcellulose (CMC-Na)).

[0192] In some embodiments, the negative electrode plate can be manufactured in the following manner: Components for manufacturing the negative electrode plate, such as a negative electrode active material, a conductive agent, an adhesive, and any other components, are dispersed in a solvent (e.g., deionized water) to form a negative electrode slurry, which is then coated on a negative electrode current collector, and the negative electrode plate is obtained after processes such as drying and cold pressing.

[0193] The electrolyte serves to conduct ions between the positive and negative electrodes. The present application does not specifically limit the type of electrolyte, which can be selected according to needs.

[0194] In some embodiments, the electrolyte is an electrolytic solution, which includes an electrolyte salt and a solvent.

[0195] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonate), lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluoro(oxalato)borate, lithium bis(oxalato)borate, lithium difluorobis(oxalato)phosphate, and lithium tetrafluoro(oxalato)phosphate.

[0196] In some embodiments, the solvent may be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, ethyl methyl sulfone, and diethyl sulfone.

[0197] In some embodiments, the electrolyte solution further optionally includes additives. For example, the additives may include an anode film-forming additive, a cathode film-forming additive, and may further include additives that can improve some performance of the battery, such as an additive that improves the overcharge performance of the battery, an additive that improves the high temperature or low temperature performance of the battery, etc.

[0198] In some embodiments, the electrode assembly further includes a separator. The present application is not particularly limited to the type of separator, and any known porous structure separator having good chemical and mechanical stability may be selected.

[0199] In some embodiments, the separator may be made of at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator may be a single layer film or a multi-layer composite film, without any particular limitation. When the separator is a multi-layer composite film, the materials of each layer may be the same or different, without any particular limitation.

[0200] In some embodiments, the positive plates, negative plates and separators can be fabricated into an electrode assembly by a winding process or a lamination process.

[0201] In some embodiments, the electrode assembly may include an outer casing, which may be used to package the electrode assembly and electrolyte.

[0202] In some embodiments, the exterior of the electrode assembly may be a hard case, such as a hard plastic case, an aluminum case, a steel case, etc. The exterior of the electrode assembly may be a pouch, such as a bag-like pouch. The pouch may be made of plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0203] The present application is not particularly limited to the shape of the electrode assembly, which may be cylindrical, rectangular or any other shape. For example, FIG. 5 shows an electrode assembly 5 with a rectangular structure as an example.

[0204] In some embodiments, referring to FIG. 6, the exterior body may include a case 51 and a cover plate 53. Here, the case 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate surround and form a receiving cavity. The case 51 has an opening communicating with the receiving cavity, and the cover plate 53 can cover the opening to seal the receiving cavity. The positive electrode plate, the negative electrode plate and the separator can form an electrode assembly 52 by a winding process or a stacking process. The electrode assembly 52 is packaged in the receiving cavity. The electrolyte is infiltrated into the electrode assembly 52. ​​The number of electrode assemblies 52 included in the electrode assembly 5 may be one or more, and can be selected by those skilled in the art according to specific actual needs.

[0205] In some embodiments, the electrode assemblies may be assembled into a battery module, and the number of electrode assemblies included in the battery module may be one or more, and the specific number can be selected by one skilled in the art according to the application and capacity of the battery module.

[0206] Fig. 7 shows an example of a battery module 4. Referring to Fig. 7, in the battery module 4, a plurality of electrode assemblies 5 may be arranged in sequence along the longitudinal direction of the battery module 4. Of course, they may be arranged in any other manner. Furthermore, the plurality of electrode assemblies 5 may be fixed by fasteners.

[0207] Optionally, the battery module 4 may further include a housing having an accommodating space, and the multiple electrode assemblies 5 are accommodated in the accommodating space.

[0208] In some embodiments, the battery modules may be further assembled into a battery pack, and the number of battery modules included in the battery pack may be one or more, and the specific number may be selected by one skilled in the art according to the application and capacity of the battery pack.

[0209] 8 and 9 show an example of a battery pack 1. Referring to Fig. 8 and Fig. 9, the battery pack 1 may include a battery box and a plurality of battery modules 4 installed in the battery box. The battery box includes an upper housing 2 and a lower housing 3, and the upper housing 2 may cover the lower housing 3 to form a sealed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.

[0210] The present application further provides a power consuming device, which includes at least one of the electrode assembly, the battery module, or the battery pack according to the present application. The electrode assembly, the battery module, or the battery pack may be used as a power source for the power consuming device, or may be used as an energy storage unit for the power consuming device. The power consuming device may include, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.

[0211] As the power consuming device, an electrode assembly, a battery module or a battery pack can be selected according to the usage demand.

[0212] 10 is an example of a power consuming device, such as a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. A battery pack or a battery module can be employed to meet the demand for high power and high energy density of the electrode assembly of the power consuming device.

[0213] Another example of the device may be a mobile phone, a tablet computer, a notebook computer, etc. This device is generally required to be thin, and employs an electrode assembly as a power source.

[0214] Working Example The following describes the examples of the present application. The examples in the following description are examples and are only used to interpret the present application, and should not be understood as limitations on the present application. If no specific techniques or conditions are specified in the examples, they are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. If no manufacturer is specified, the reagents or equipment used are all ordinary products available on the market.

[0215] Example 1 Adhesive manufacturing Step 1: 800g deionized water, 3g sodium perfluoropolyether carboxylate, and 1.5g diisopropyl peroxydicarbonate are added to a 5L high-pressure reactor A, stirring is started, vacuum is drawn, and the gas is replaced with nitrogen gas. Vinylidene fluoride and hexafluoropropylene gas are introduced into the high-pressure reactor A, and the pressure in the high-pressure reactor is increased to 3.5MP. The reaction temperature of the system is increased to 75°C, and polymerization reaction is started. When the pressure in the high-pressure reactor A drops to 3.0MP, vinylidene fluoride and hexafluoropropylene gas are continued to be introduced to control the pressure in the high-pressure reactor A at 3.0-3.5MP. The amount of vinylidene fluoride and hexafluoropropylene introduced is 200g in total. When the pressure drops to 2MP or less, the reaction is stopped to obtain a seed emulsion. Step 2: Add 75.24g of methyl acrylate, 18.55g of acrylonitrile, and 6.21g of acrylamide to reactor B, making the molar ratio of the three 1:0.4:0.1; add 3.6g of sodium dodecylsulfonate and 100g of deionized water; thoroughly stir to disperse and emulsify, to obtain a shell layer monomer pre-emulsion; Step 3: Add 100g of deionized water into the high-pressure reactor A, and under high-speed stirring, use a peristaltic pump to slowly drip in the shell layer monomer pre-emulsion and initiator solution (0.2g of initiator potassium persulfate is dissolved in deionized water to form a solution) in the reactor B. After dripping is completed, the temperature is raised to 90°C and the reaction is kept at 90°C for 0.5 hours, cooled to 40°C, and the pH is adjusted to 7-8 with ammonia water, and then filtered and discharged.

[0216] Separator manufacturing A commercially available PP-PE copolymer microporous film with a thickness of 20 μm and an average pore diameter of 80 nm was used as the substrate. The adhesive prepared as described above was uniformly mixed with deionized water under stirring to obtain a slurry (solid content 20%). The slurry was uniformly applied to two surfaces of the substrate, dried to remove the solvent, and the composition was coated on the substrate at a coating density of 1.0 g / m2. 2 Thus, a separator was obtained.

[0217] Positive electrode plate manufacturing Polyvinylidene fluoride (PVDF), lithium iron phosphate (LFP), carbon black as a conductive agent, and N-methylpyrrolidone (NMP) were mixed homogeneously in a mass ratio of 1.2:58.38:0.42:40, and then prepared as a positive electrode slurry. This positive electrode slurry was mixed at 200 g / m 2 The aluminum foil positive electrode current collector was uniformly coated with the coating material in an amount of 0.1 to 1000g, and then dried, cold pressed, and slit to obtain a positive electrode plate.

[0218] Negative electrode plate manufacturing Artificial graphite, acetylene black as a conductive agent, styrene butadiene rubber (SBR) as an adhesive, and sodium carboxymethylcellulose (CMC-Na) as a thickener were added to deionized water in a mass ratio of 96.2:1.0:1.6:1.2, thoroughly stirred to mix uniformly, and then anode slurry (solid content 63%) was produced. This anode slurry was 98 g / m 2 The negative electrode current collector copper foil was coated with the coating material in an amount of 0.1g / g, and then dried, cold pressed, and slit to obtain a negative electrode plate.

[0219] Electrolyte production At 25°C, ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain a mixed solvent, and LiPF6 is dissolved in the mixed solvent to obtain an electrolyte solution, in which the concentration of LiPF6 is 1 mol / L.

[0220] Battery cell manufacturing The positive electrode plate, separator, and negative electrode plate were stacked in order, wound, and pre-press molded (the separator and the electrode plate were bonded during this period) to obtain an electrode assembly. The electrode assembly was then placed in an outer casing, the above-prepared electrolyte solution was added, and a battery cell was obtained after going through processes such as packaging, standing, chemical conversion, and aging.

[0221] The parameters (eg, as shown in Table 1) of Example 1 were changed to obtain the experimental data of Examples 2 to 17.

[0222] Comparative Example 1: Preparation steps of polyvinylidene fluoride polymer Add 200g of deionized water, 1g of sodium perfluoropolyether carboxylate, and 0.5g of diisopropyl peroxydicarbonate to the high-pressure reactor, start stirring, evacuate, replace gas with nitrogen gas, introduce vinylidene fluoride and hexafluoropropylene gas into the high-pressure reactor, increase the pressure in the autoclave to 3.5MP, increase the reaction temperature of the system to 75 ° C, start polymerization reaction, when the pressure in the high-pressure reactor drops to 3.0MP, continue to introduce vinylidene fluoride and hexafluoropropylene gas, control the pressure in the high-pressure reactor to 3.0-3.5MP, the amount of vinylidene fluoride and hexafluoropropylene input is 200g in total, and when the pressure drops to 2MP or less, stop the reaction, filter, and discharge.

[0223] Comparative Example 2: Steps for preparing a polymer obtained by polymerizing a first flexible monomer Into a three-neck flask, add 752.4g of methyl acrylate, 36g of sodium dodecylsulfonate, and 1.2kg of deionized water, and thoroughly stir to disperse and emulsify. Heat to 70°C, add initiator solution (a solution formed by dissolving 0.6g of potassium persulfate in deionized water), and stir for 30min to react. Continue to heat to 80°C, slowly drip initiator solution (a solution formed by dissolving 1.2g of potassium persulfate in 100g of deionized water) with a peristaltic pump. After dripping is complete, heat to 90°C and react for 0.5h while keeping the temperature, cool to 40°C, adjust pH to 7 with ammonia water, stop the reaction, filter, and discharge.

[0224] Comparative Example 3: Steps for preparing a polymer obtained by polymerizing a second polymerizable polar monomer Deionized water and a certain percentage of initiator were added to a three-neck flask equipped with a reflux condenser, a thermometer, and a magnetic stirrer. After stirring uniformly at room temperature, the temperature was raised to the set temperature to promote the decomposition of the initiator. About half an hour after the temperature became constant, a peristaltic pump was used to control the concentration of acrylonitrile entering the polymerization system, and the monomer was dripped into the water in a small droplet manner to achieve the polymerization reaction. After the monomer dripping was completed, the reaction was continued at a constant temperature for a certain period of time while stirring. After the reaction was completed, the three-neck flask was transferred to air and cooled to room temperature to stop the reaction, filtered, and discharged.

[0225] Comparative Example 4: Steps for Producing a Polymer Obtained by Polymerizing a Third Polymerization Molecular Weight Control Monomer First, 120g of water was added to 30g-90g of acrylamide monomer to prepare an acrylamide solution, and 0.02g-1g of persulfate was dissolved in 30g of water to obtain an initiator solution. 37.5g of isopropyl alcohol solvent was added to a 250mL four-neck reaction flask, opened and stirred, the stirring speed was set to 200r / min, the temperature was raised until reflux, and the monomer solution and the initiator solution were continuously dripped, the dripping speed was controlled, and the dripping time was set to 120min. The reflux reaction was maintained for 2h, the isopropyl alcohol was distilled, and a polyacrylamide solution was obtained, filtered, and discharged.

[0226] Comparative Example 5: Mixing and polymerizing polyvinylidene fluoride and polyacrylate The polyvinylidene fluoride solution prepared in Comparative Example 1 and the polyacrylate solution prepared in Comparative Example 2 were mixed in a mass ratio of 1:1 and stirred uniformly to obtain a blend solution of polyvinylidene fluoride and polyacrylate, which was then filtered and discharged.

[0227] As shown in Tables 1 and 2, in Examples 1 to 4, 16 and 17, the ratio of the three types of polymers in the core layer was changed while other conditions were kept unchanged, and in Examples 5 to 8 and 12 to 15, the masses of the core layer and shell layer were changed while other conditions were kept unchanged.

[0228] As shown in Table 3, Comparative Example 1 is an adhesive obtained by producing a polyvinylidene fluoride polymer, Comparative Example 2 is an adhesive obtained by producing an acrylate-based polymer, Comparative Example 3 is an adhesive obtained by producing an acrylonitrile-based polymer, Comparative Example 4 is an adhesive obtained by producing an acrylamide-based polymer, and Comparative Example 5 is an adhesive obtained by mixing polyvinylidene fluoride and polyacrylate and polymerizing the mixture to produce a polymer.

[0229] [Table 1]

[0230] [Table 2]

[0231] [Table 3]

[0232] Performance Test: 1. Separator and electrode plate adhesion test step The battery plate and separator were stacked and placed in a heat press, and the heat press parameters were set to 25°C, 10t, and 30s to produce a bonded separator / positive plate sample, which was then cut into a 150 x 20mm rectangular spline. One side of the rectangular spline plate was attached to a steel plate with double-sided adhesive, and the separator and plate were separated by 2cm along the length at one end of the rectangular spline to produce a test sample.

[0233] The steel plate was held horizontally and fixed with the lower fixture of a universal testing machine (Model CTM2100, manufactured by Xie Wei Cheng Instrument Manufacturing (Shanghai) Co., Ltd.), the peeled end of the separator was fixed with the upper fixture of the universal testing machine, and a tensile machine was connected. The test conditions were set to a tensile rate of 20 mm / min and a horizontal tensile of 10 cm. When the tensile force became stable, the tensile force value was recorded, and the adhesive strength between the separator and the electrode plate was obtained from the ratio of the tensile force value to the sample width.

[0234] 2. Large fixture cycle performance test step A jig force of 10,000N is applied to the outside of the battery core, and a cycle test is performed in this state. The test steps are as follows: At 25°C, the battery produced in Example 1 is charged at a constant current of 1 / 3C to 3.8V, then charged at a constant voltage of 3.8V until the current becomes 0.05C, left for 5 minutes, and discharged at 1 / 3C to 2.0V. The discharge capacity obtained is the initial capacity C0. The above steps are repeated for the same battery, and the discharge capacity Cn of the battery after the nth cycle is recorded at the same time. The battery capacity retention rate after each cycle Pn = (Cn / C0) x 100%. That is, the battery capacity retention rate after 500 cycles can embody the difference in cycle performance.

[0235] [Table 4]

[0236] As shown in Table 4, the battery cores obtained using the adhesives in Examples 1 to 17 have good adhesive strength between the separator and the electrode plates, but the battery cores obtained using the adhesives in Comparative Examples 1 to 5 have inferior adhesive strength between the separator and the electrode plates to those in Examples 1 to 17. It has been explained that the adhesive performance of the adhesives in Examples 1 to 17 is superior to that of the adhesives in Comparative Examples 1 to 5. And, the battery cycle performance in Examples 1 to 17 is superior to that of Comparative Examples 1 to 5. It has been explained that when the adhesive performance of an adhesive is improved, the cycle performance of a battery can be effectively improved by using this adhesive for a battery separator.

[0237] The above is merely a preferred embodiment of the present application, and does not limit the patent scope of the present application. Any equivalent structural transformation made using the contents of the specification and drawings of the present application in accordance with the application concept of the present application, or any direct or indirect operation in other related technical fields, is within the patent protection scope of the present application. [Explanation of symbols]

[0238] Code Name Code Name 1 Battery Pack 51 Case 2 Upper housing 52 Electrode assembly 3 Lower housing 53 Top cover assembly 4 Battery module 6 Core layer structure 5 Electrode assembly 7 Shell layer structure

Claims

1. 1. An adhesive comprising: a core layer structure; and a shell layer structure provided on a surface of the core layer structure, the shell layer structure comprising a polyacrylate-based polymer, and the core layer structure comprising a polyvinylidene fluoride polymer.

2. The adhesive of claim 1 , wherein the shell layer structure includes a plurality of cases, the plurality of cases being spaced apart on a surface of the core layer structure.

3. The adhesive of claim 1 or 2, wherein the mass ratio of the polyvinylidene fluoride polymer to the polyacrylate-based polymer is (2-100):1, optionally (10-80):

1.

4. The adhesive of any one of claims 1 to 3, wherein the adhesive has a volume average particle size Dv50 of 0.5 μm-50 μm, optionally 7 μm-8 μm.

5. The adhesive according to claim 1 , wherein constituent monomers of the polyacrylate polymer include a first polymerizable flexible monomer, a second polymerizable polar monomer, and a third polymerizable molecular weight adjusting monomer.

6. 6. The adhesive of claim 5, wherein the molar ratio of the first polymerizable flexible monomer to the second polymerizable polar monomer to the third polymerizable molecular weight adjusting monomer is 1:(0.01-0.8):(0.01-0.15), optionally 1:(0.05-0.7):(0.05-0.12).

7. 7. The adhesive according to claim 5 or 6, wherein the structure of the first polymerizable flexible monomer contains an ester bond, the structure of the second polymerizable polar monomer contains a cyano group, and the structure of the third polymerizable molecular weight adjusting monomer contains an amide bond.

8. 8. The adhesive of claim 5, wherein the first polymerizable flexible monomer is an acrylate-based monomer, the second polymerizable polar monomer is an acrylonitrile-based monomer, and the third polymerizable molecular weight adjusting monomer is an acrylamide-based monomer.

9. The acrylate monomer includes at least one of methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, n-propyl acrylate, cyclohexyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, isobornyl methacrylate, lauryl methacrylate, 2-hydroxyethyl methacrylate, and 2-hydroxypropyl methacrylate; And / or, the acrylonitrile-based monomer includes at least one of acrylonitrile and methacrylonitrile, And / or the adhesive according to claim 8, wherein the acrylamide-based monomer includes at least one of acrylamide, N-methylolacrylamide, and N-butoxymethacrylamide.

10. 10. The adhesive of claim 1, wherein the polyvinylidene fluoride polymer comprises at least one of a vinylidene fluoride polymer, a vinylidene fluoride-hexafluoropropylene copolymer, a vinylidene fluoride-pentafluoropropylene copolymer, a vinylidene fluoride-tetrafluoropropylene copolymer, a vinylidene fluoride-trifluoropropylene copolymer, a vinylidene fluoride-perfluorobutene copolymer, a vinylidene fluoride-tetrafluoroethylene copolymer, a vinylidene fluoride-trifluoroethylene copolymer, a vinylidene fluoride-trifluorochloroethylene copolymer, or a vinylidene fluoride-vinyl fluoride copolymer.

11. A method for producing an adhesive, comprising the steps of: Add water, an emulsifier, an initiator, and constituent monomers of polyvinylidene fluoride polymer into a reaction vessel, stir, and heat under reaction pressure to polymerize, thereby obtaining a seed emulsion, which is kept as a reserve; mixing and stirring water, an emulsifier, and a constituent monomer of a polyacrylate-based polymer to obtain a shell layer monomer pre-emulsion, which is used as a reserve; adding the shell layer monomer pre-emulsion and an initiator to the seed emulsion, and stirring and heating to react with each other to obtain an adhesive having a core-shell structure.

12. The method for producing an adhesive according to claim 11, wherein the ratio of the constituent monomer mass of the polyvinylidene fluoride polymer to the constituent monomer mass of the polyacrylate-based polymer is (2 to 100):1, and optionally (10 to 80):

1.

13. The constituent monomer of the polyvinylidene fluoride polymer includes vinylidene fluoride, Alternatively, the method for producing an adhesive according to claim 11 or 12, wherein the constituent monomers of the polyvinylidene fluoride polymer include at least one of vinylidene fluoride, hexafluoropropylene, pentafluoropropylene, tetrafluoropropylene, trifluoropropylene, perfluorobutene, tetrafluoroethylene, trifluoroethylene, trifluorochloroethylene, and vinyl fluoride.

14. A separator comprising the adhesive according to any one of claims 1 to 10 or an adhesive produced by the method for producing an adhesive according to any one of claims 11 to 13.

15. An electrode assembly comprising the separator of claim 14.

16. A battery cell comprising the electrode assembly of claim 15.

17. A battery comprising the battery cell of claim 16.

18. 18. A power consuming device comprising a battery cell according to claim 16 or a battery according to claim 17.

Citation Information

Patent Citations

  • Core-shell structure polymer, preparation method and application thereof, positive electrode slurry, secondary battery, battery module, battery pack and electric device

    CN115117356A